2014
DOI: 10.12669/pjms.302.4375
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inferior vena cava diameter measured by bedside ultrasonography and central venous pressure value

Abstract: Objective: We aimed to present inferior vena cava (IVC) diameter as a guiding method for detection of relationship between IVC diameter measured noninvasively with the help of ultrasonography (USG) and central venous pressure (CVP) and evaluation of patient's intravascular volume status. Methods: Patients over the age of 18, to whom a central venous catheter was inserted to their subclavian vein or internal jugular vein were included in our study. IVC diameter measurements were recorded in millimeters followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…There are few studies on the size of the IVC and its relationship to respiratory movements [1,2,10] or with central venous pressure [7,11,20] , and no studies correlating these data with the intravenous abdominal pressure. Using realhave concluded that three-dimensional CT is the most accurate method to study filter position and to assess safety Phlebography during the Valsalva maneuver that shows distribution of the contrast medium to renal and iliac veins; C: Computational study of inferior vena cava migration forces using an experimental set up and finite element simulation during the Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies on the size of the IVC and its relationship to respiratory movements [1,2,10] or with central venous pressure [7,11,20] , and no studies correlating these data with the intravenous abdominal pressure. Using realhave concluded that three-dimensional CT is the most accurate method to study filter position and to assess safety Phlebography during the Valsalva maneuver that shows distribution of the contrast medium to renal and iliac veins; C: Computational study of inferior vena cava migration forces using an experimental set up and finite element simulation during the Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…There is little data in the literature relating biometrics and hemodynamics of the IVC [9][10][11] . Kaura et al [12] studied the biometrics of the IVC and concluded that venography alone is not an ideal method to assess true IVC diameters.…”
Section: Introductionmentioning
confidence: 99%
“…According to Lorenzo et al (2012), the size of the inferior vena cava (IVC) is closely related to the results of the CVP assessment. The study states that measuring IVC diameter through ultrasonography can be used as determination of CVP values in indicating fluid volume status (Citilcioglu, 2014;Wiwatworapan, Ratanajaratroj & Sookananchai, 2012). In the right side HoB 30o position, IVC has kinking because the close IVC to the right facilitates suppression by the kidneys, and anatomically the location of the heart in the left hemithorax, when tilted to the right, the left side of the heart pushes to the right which causes the diameter of the right atrial space decreased, so that the volume of blood / venous return has decreased so that the impact on the decrease in blood pressure is greater when compared with the left lateral position (Hazebroek & Bonjer, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IVCD has been shown in previous studies to reflect the intravascular volume in HD patients and to correlate well with invasive methods like measurement of CVP for estimation of fluid volume. 9 This study has been done to measure IVCD and calculate IVC-CI to categorize the fluid status of regular hemodialysis patients. In this study, IVCe and IVCi were measured and the collapsibility indices of IVC calculated which correlated well with the amount of ultrafiltration done during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%